Evolution of antibiotic resistance in Salmonella enterica serovar typhimurium strains isolated in the Czech Republic between 1984 and 2002 - Faldynova, M; Pravcova, M; Sisak, F; Havlickova, H; Kolackova, I; Cizek, A; Karpiskova, R; Rychlik, I (Antimicrobial agents and chemotherapy, 2003)
In a collection of 66 Salmonella enterica serovar Typhimurium strains isolated between 1984 and 2002 in the Czech Republic, genes coding for antibiotic resistance were determined by using specific PCRs. We found that the pentadrug-resistant ACSSuT clone first appeared in the Czech Republic in 1990. A new variant of the aadA gene designated aadA21 is described, the 5' end of which was identical to aadA2 and the 3' end of which was identical to aadA1.
Keywords: Microbial Sensitivity Tests; DNA bakterií; Humans; mnohočetná bakteriální léková rezistence; mikrobiální testy citlivosti; lidé; hospodářská zvířata; zvířata; Drug Resistance, Multiple, Bacterial; DNA, Bacterial; Retrospective Studies; Animals, Domestic; salmonelóza; Salmonella typhimurium; Czech Republic; polymerázová řetězová reakce; Polymerase Chain Reaction; retrospektivní studie; Animals; Česká republika; Salmonella Infections